Incidence of Root-Knot Disease in Tomato and Potato and Identity of the Causal Species in the Western Region of the Libyan Jamahiriya - DABAJ, KHALIFA H.; KHAN, M. WAJID (The Libyan Journal of Agriculture, 2023)
Root-knot nematodes are considered one of the most important group of plant parasites. They are distributed world-wide and infect a variety of food and fibre crops. Little information is available about root-knot nematodes in the Libyan Jamahiriya. An attempt has been made to study some aspects of root-knot nematodes infecting tomatoes and potatoes in western regions of the country. Surveying tomato and potato fields in ten localities from Zawia to El-Khoms revealed that tomatoes were more affected by root-knot nematode disease than potatoes. Meloidogyne javanica and M. incognita were identified as the species of root-knot nematodes present on tomatoes and potatoes in this region. M. javanica was the dominant species, while M. incognita was found only in certain localities. Two races of M. incognita were identified; they were designated Race 1 and Race 2. Race 1 was found at El-Khoms while Race 2. in Ameriya. Airport Road and Zawia.